Neonatal Immune Responses to Respiratory Viruses - Eddens, Taylor; Parks, Olivia B.; Williams, John V. (Frontiers in Immunology, 2022)
Respiratory tract infections are a leading cause of morbidity and mortality in newborns, infants, and young children. These early life infections present a formidable immunologic challenge with a number of possibly conflicting goals: simultaneously eliminate the acute pathogen, preserve the primary gas-exchange function of the lung parenchyma in a developing lung, and limit long-term sequelae of both the infection and the inflammatory response. The latter has been most well studied in the context of childhood asthma, where multiple epidemiologic studies have linked early life viral infection with subsequent bronchospasm. This review will focus on the clinical relevance of respiratory syncytial virus (RSV), human metapneumovirus (HMPV), and rhinovirus (RV), examining the protective and pathogenic host responses within the neonate, the long-term sequelae of early life infection, and treatment and prevention strategies.